Influence of Patient, Visit, and Oral Health Factors on Dental Service Provision - David S. Brennan, MPH, PhD; A. John Spencer, MDSc, MPH, PhD (Blackwell Synergy, 2002)
Service provision should reflect the oral health of the patient. However, patient and visit factors may influence service patterns and the appropriateness of care delivered. The aim of this study was to examine factors associated with variation in dental services and to assess whether variation by patient and visit characteristics persisted after controlling for oral health status